Tenuta del registro formale nella comunicazione accademica scritta in italiano L1 e L2 - Pagliara, Francesca (Linguistik Online, 2025)
This study analyses the level of formality in e-mails sent by 378 university students (246 Italian and 132 international) to lecturers, with the aim of observing the management of the formal register in academic communication via e-mail. The analysis focuses on the detection of specific linguistic features such as punctuation, use of polite pronouns, informal or spoken syntactic structures. The results show that there are common features in the ability to manage the formal register in the written production of L1 and L2 students, although significant differences emerge in the use of punctuation and polite pronouns, mostly due to interlinguistic interference. These findings have implications for the design of teaching interventions, suggesting that an academic writing course should be designed with an emphasis on awareness of linguistic variation.